Perlindungan Konsumen atas Wanprestasi yang Disebabkan oleh Kelalaian Penyedia Jasa Sewa Fotografer yang Menyebabkan File Corrupt - Alfiarini, Jelita; Apriani, Rani; Iman, Candra Hayatul (Jurnal Ilmiah Wahana Pendidikan, 2025)
In economic activities in society, rental activities are an alternative for some people to get the benefits of goods and/or services at affordable costs. However, the actions of business actors that cause losses to consumers cannot be avoided, thereby causing consumer losses. Through the case of a photographer rental service which causes photo files to become corrupted, this research aims to find out how the Consumer Protection Law provides protection for consumers against defaults caused by negligence of photographer services which causes files to become corrupted. This research uses normative juridical research methods with library study data collection techniques. Based on the research results, the Consumer Protection Law provides full protection for consumers who suffer losses due to defaults committed by business actors and the resulting consequences, namely legal consequences in the form of administrative sanctions and non-legal consequences in the form of social sanctions.